Optimisation in economic analysis - Mills, Gordon (London ; Boston : Allen & Unwin, 1984)
One of the fundamental economic problems is one of making the best use of limited resources. As a result, mathematical optimisation methods play a crucial role in economic theory. Covering the use of such methods in applied and policy contexts, this book deals not only with the main techniques (linear programming, nonlinear optimisation and dynamic programming), but also emphasizes the art of model-building and discusses fields such as optimisation over time.
Includes bibliographical references and index.
sms 28/05/2018
Loans
Keywords: Mathematical optimization; Economics, Mathematical